Low complexity routing algorithm for rearrangeable switching networks - Chakrabarty, Amitabha; Collier, Martin J. (© 2013 IEEE, 2016)
This conference paper was presented in the 27th IEEE International Conference on Advanced Information Networking and Applications, AINA 2013; Barcelona; Spain; 25 March 2013 through 28 March 2013 [© 2013 IEEE] The conference paper's definite version is available at: http://dx.doi.org/110.1109/AINA.2013.55